한국의 개발협력사업과 포스트개발론적 접근: 탄자니아 사례를 중심으로 - 박민철 (국제개발협력연구, 10(1), 2018)
연구목적: 본 연구는 기존의 정형화된 공여국 시각의 접근이 수원국의 경제 발전과 수원국 국민의 삶의 질 향상에 실질적인 기여를 하고 있는 지에 대한 문제제기를 바탕으로, 탄자니아 내 한국의 개발협력사업을 포스트개발론의 관점에서 고찰하고 분석하는데 목적을 두고 있다. 연구의 중요성: 아직까지 국내의 탄자니아에 대한 개발협력정책이나 사업에 관한 연구는 공여국 관점의 정량적 접근이 주류를 이루고 있다 보니, 다양한 이론을 기반으로 한 연구 분석이 활발히 이루어지지 못하고 있다. 따라서 탄자니아에 대한 한국의 무상원조사업을 포스트개발론의 시각으로 접근한 본 논문의 질적 연구는 기존의 연구에 비해 그 차별적인 특성을 지니고 있다. 연구방법론: 본 연구는 통계와 수치 등 원조공여국의 시각과 정량적 관점으로 접근하는 방식을지양하고 기존 개발 패러다임의 시각에서 벗어나 지역 단위의 참여, 풀뿌리 접근, 문화 다양성 등을 핵심 개념으로 수용하는 포스트개발론의 관점에서 한국의 탄자니아 개발협력사업을 분석하였다. 연구결과: 한국의 탄자니아에 대한 개발협력사업의 주요 목표는 하드웨어적 사업발굴과 물적 수단 기반의 지원방식을 통해 경제적, 사회적 인프라를 구축하고 한국의 개발경험을 전수하는 데 중점을 두고 있다. 또한 수원국의 현지 상황과 지역성을 반영할 수 있는 현지 원조활동 역량을 제대로 갖추고 있지 못하다. 이는 결과적으로 탄자니아에 대한 원조효과성을 저해할 수 있다. 결론 및 시사점: 국제원조공동체의 보편적 가치와 원칙에 어긋나지 않으면서도 한국만의 고유한 개발협력 가치를 도출하기 위한 고민이 필요한 시점이다. 따라서 원조의 최종수혜자를 개발협력 사업 전 과정에 적극적으로 참여시켜, 현지의 개발 관점을 최대한 반영할 수 있는 새로운 개발 패러다임이 요구된다고 할 수 있다. Purpose: This paper explores to review and analyze Korea's development cooperation projects in Tanzania from the perspective of post-development theory. And it raises the question whether the donors' development cooperation approaches have contributed to economic growth and quality of life in the recipient country. Originality: In Korea, studies on development cooperation policies and projects toward Tanzania are mainly conducted on quantitative approach from the donor perspective. So research analysis based on various theories is not yet actively carried out. This study is a qualitative research approach to the grant aid projects from the perspective of post-development theory. And its new attempt has distinctive characteristics compared with the existing studies. Methodology: This paper examined Korea’s development cooperation projects in Tanzania from the perspective of post-development theory. Post-development theory emphasizes the involvement of local communities in consideration of their historical context and social situation, and places importance on grassroots activities and cultural diversity. Result: The main objectives of Korea's development cooperation project in Tanzania are focused on establishing economic and social infrastructure and transferring the development experience of Korea by searching for hardware projects and supporting material resources. The systematic management of the development cooperation projects is still insufficient to reflect the local situation and to assess the needs of communities and the resources available to them. This can ultimately hinder aid effectiveness of Korea's development cooperation project in Tanzania. Conclusion and Implication: It is time for Korea to seek its own development paradigm, which does not violate the universal values and principles of the international aid community, but pursues the aid method from below and guarantees active participation of the final beneficiaries. Therefore, a new development paradigm is needed to strengthen the required capacities of local people to realize the development of local communities and to localize development plans. KCI Citation Count: 5